2002
DOI: 10.1074/jbc.m108366200
|View full text |Cite
|
Sign up to set email alerts
|

MEK Kinase 1 Induces Mitochondrial Permeability Transition Leading to Apoptosis Independent of Cytochrome cRelease

Abstract: Induction of apoptosis often converges on the mitochondria to induce permeability transition and release of apoptotic proteins into the cytoplasm resulting in the biochemical and morphological alteration of apoptosis. Activation of a serine threonine kinase MEK kinase 1 (MEKK1) is involved in the induction of apoptosis. Expression of a kinase-inactive MEKK1 blocks genotoxininduced apoptosis. Upon apoptotic stimulation, MEKK1 is cleaved into a 91-kDa kinase fragment that further induces an apoptotic response. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…This conclusion is consistent with previous studies suggesting that MPT pore opening is unlikely to occur under the low pH conditions of ischemia and is more likely to occur after reperfusion (18,20); indeed, we observed a fall in ⌬⌿ m during ischemia before reperfusion. However, other investigators have used higher (10,16) or lower (38) concentrations of cyclosporin A to inhibit the opening of that pore, so it is not clear whether protection would have been observed at different concentrations or with other inhibitors of the MPT pore.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is consistent with previous studies suggesting that MPT pore opening is unlikely to occur under the low pH conditions of ischemia and is more likely to occur after reperfusion (18,20); indeed, we observed a fall in ⌬⌿ m during ischemia before reperfusion. However, other investigators have used higher (10,16) or lower (38) concentrations of cyclosporin A to inhibit the opening of that pore, so it is not clear whether protection would have been observed at different concentrations or with other inhibitors of the MPT pore.…”
Section: Discussionmentioning
confidence: 99%
“…MEK kinase 1 (MEKK1) is a serine/threonine kinase that participates in the induction of apoptosis [14][15][16][17][18][19][20]. MEKK1 has been found present in the IKK complex and activates the NF-jB signalling pathway [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous JNK has been shown to phosphorylate many mitochondrial proteins during apoptosis (23); however, not all apoptotic agents trigger a sequential activation of JNK and mitochondrial pathways (25,26). Our prior studies showed that dexamethasone-induced apoptosis in MM.1S occurs independent of JNK activation, but is associated with Smac release (18).…”
Section: Role Of Mitochondrial Protein Smac In Myeloma 17595mentioning
confidence: 99%